The development reader - Chari, Sharad; Corbridge, Stuart (London ; New York : Routledge, 2008)
Comprising writings ordered around intentional and imminent 'development', this reader offers a compendium of classical and contemporary debates on development: Adam Smith and Karl Marx meet, among others, Robert Wade, Amartya Sen and Jeffrey Sachs.
Keywords: Economic development; Economic policy